Understanding the Dynamics of Sex-Specific Responses Driven by Grassland Management: Using Syrphids as a Model Insect Group - Raja Imran Hussain; Daniela Ablinger; Walter Starz; Jürgen Kurt Friedel; Thomas Frank (Land, 2024)
Grassland ecosystems, managed by various grassland managements strategies, are the world’s most important land use. However, insect’s sex-specific responses within the context of grassland management have never been considered before. Therefore, our aim was to expand the understanding to the dynamics of grassland managements that drive sex-specific responses by using syrphids as a model insect group. We hypothesize that (1) male and female syrphids exhibit differential habitat preferences in grassland managements, (2) abundance and activity of male and female syrphid levels are influenced by vegetation structure in grassland habitats. Extensive and intensive grassland exhibited significantly different male and female syrphid abundance compared to abandoned grassland. Surprisingly, grassland management had a significant impact on male syrphids richness only, not on female. Flower cover significantly increased male and female syrphid abundance and richness. However, plant height significantly increased female syrphid abundance and richness only. Interestingly, abandoned grassland supports a higher amount of unique female syrphids than male syrphids. The dynamics of grassland management are not unidirectional, but they are multifaceted and multidirectional. Considering the importance of sex-specific responses by insects can provide a more comprehensive understanding of dynamics of grassland managements.